Structural/functional analysis of complement proteins and inhibitions - Xu, Xin (Kansas State University, 2022)
The complement system is an important component of innate immunity that fulfills diverse roles in defense and homeostasis, typically conferring protection against accumulating debris and eliminating pathogens. Overactivation or inappropriate activation of the complement system contributes to many inflammatory diseases. Tight regulation and inhibition of complement activators are paramount to prevent inappropriate activation, which has led to an emphasis on the development of therapeutic complement inhibitors. Activation of the central complement component, C3, is required for amplification of complement and is achieved through two different multi-subunit proteases called C3 convertases. Of these, the so-called Alternative Pathway (AP) C3 Convertase is responsible for a majority of the C3 activation products in vivo, which renders it an attractive target for inhibitor discovery. Moreover, among many components in the complement system, another molecule, factor H (FH), whose principal function is to inhibit the activity of the complement system, is a complement control protein. FH associates with the surface of human cells, thereby it ensures the complement system is directed towards pathogen rather than host cells. An opportunistic pathogen, Group B Streptococcus (GBS), colonizes the gastrointestinal and vaginal epithelium of a large population of healthy women. Therefore, sometimes it causes ascending intrauterine infection during parturition and creates a risk of serious disease in newborn infants. The β protein is a large, multifunctional surface protein of GBS being investigated as a potential vaccine candidate. As a component of innate immunity, the complement system plays a role in defense against GBS. It has been previously reported that the GBS β protein binds to FH, yet how this occurs at the molecular level remains unclear. In this study, we defined the FH binding site on β protein using a combination of structural and functional analysis. We also identified and characterized two Slow Off-rate Modified DNA Aptamers (SOMAmers) that inhibit the AP by binding to factor B (FB), the essential pro-protease of the AP. Together, our studies have defined the FH binding site within the GBS β protein and suggested that molecules that target this site may interfere with FH binding at the GBS cell surface. Ultimately, this work could inform vaccine development and promote our understanding of the β protein in the pathogenesis of Streptococcal diseases. The results also demonstrated potent inhibition of the AP by SOMAmers and expanded the pipeline of FB-binding molecules with favorable pharmacologic properties.
Keywords: Complement system